ANALISIS SWOT MENGENAI PENGEMBANGAN ASURANSI SYARIAH DI INDONESIA: STUDI LITERATUR - Zainarti Zainarti; Dinda Dia (CV. ADIBA AISHA AMIRA, 2024)
SWOT analysis plays a role in the development of Islamic insurance by helping to identify strengths, weaknesses, opportunities, and threats. This analysis can be used to: Understanding the condition of Islamic insurance, Knowing the potential and challenges faced, Designing strategies to increase market penetration, Expanding public understanding of the benefits of Islamic insurance. The research objective is to analyze the role of SWOT in the development of Islamic insurance through literature studies or previous research. The research method used is qualitative research with a literature approach as an approach in this research study. Based on the research findings, the problems in insurance development are low Islamic financial literacy, limited human resources, lack of product innovation, limited infrastructure and technology. dependence on macroeconomics. SWOT analysis plays an important role in the development of the insurance sector by helping companies identify internal and external factors that affect performance